How can we help family carers manage pain medicines for patients with advanced cancer? A systematic review of intervention studies - Latter, Sue (BMJ Support Palliat Care, 2016)
BACKGROUND: Family carers play a significant role in managing pain and associated medicines for people with advanced cancer. Research indicates that carers often feel inadequately prepared for the tasks involved, which may impact on carers’ and patients’ emotional state as well as the achievement of optimal pain control. However, little is known about effective methods of supporting family carers with cancer pain medicines. AIMS: To systematically identify and review studies of interventions to help carers manage medicines for pain in advanced cancer. To identify implications for practice and research. METHOD: A systematic literature search of databases (MEDLINE, CINAHL, PsycINFO and AMED) was carried out to identify studies of pain medication management interventions that involved family carers of patients with advanced cancer, and reported specific outcomes for family carers. Patient pain outcomes were also sought. Studies were quality appraised; key aspects of study design, interventions and outcomes were compared and a narrative synthesis of findings developed. RESULTS: 8 studies were included; all had significant methodological limitations. The majority reported improvements in family carer knowledge and/or self-efficacy for managing pain medicines; no effect on patient pain outcomes; and no adverse effects. It was not possible to discern any association between particular intervention characteristics and family carer outcomes. CONCLUSIONS: Current evidence is limited, but overall suggests face-to-face educational interventions supported by written and/or other resources have potential to improve carers’ knowledge and self-efficacy for pain management. Further research is needed to identify how best to help family carers manage pain medicines for patients with advanced cancer.